Teacher Readiness for Implementing Sustainable Education: A Comparative Synthesis of Predictive Factors Across Diverse Educational Contexts - Dwi Sulisworo; Ika Maryani; Siti Mahsanah Budijati (The Indonesian Institute of Science and Technology Research, 2025)
Teacher readiness is a critical determinant of effective implementation of Education for Sustainable Development (ESD) across global educational systems. This study synthesizes evidence from ten international studies involving more than 7,000 teachers to examine the factors that predict readiness for sustainable education and how these predictors vary across different contexts. Using a systematic semantic search, screening, and structured data extraction process, the review identifies four overarching domains shaping readiness: individual characteristics, knowledge and skills, attitudes and environmental commitment, and institutional and system-level factors. Findings reveal that demographic variables such as age, gender, and teaching experience exert limited influence, while disciplinary background, sustainability knowledge, and technological–pedagogical competence demonstrate stronger predictive power. Notably, self-efficacy and personal engagement in sustainable behaviors emerge as dominant predictors, especially in systems with greater ESD maturity. Institutional conditions—including leadership support, resource availability, school culture, and policy alignment—further moderate the translation of individual readiness into classroom practice. The review highlights significant gaps, particularly the absence of studies comparing high-performing and low-performing systems directly, and the inconsistent provision of discipline-specific professional development. The study concludes by emphasizing the need for a holistic, context-sensitive approach to strengthening teacher readiness as a foundation for advancing sustainable education globally.